Conceptualisations and research on graduate competencies for the changing workplace: the case of Malaysia - Abdul Rahman, Shukran; Yew Lie, Koo (2013)
Among the key issues in higher education is that of graduate competencies. Policies and initiatives Efforts have been made by National Governments, agencies and Higher Learning Institutions (HLIs) to produce competent graduates for the world of the workplace through increasingly iimproved curricula, and other initiatives designed to promote the acquisition of competencies (functional and generic knowledge, skills, abilities, and other desirable characteristics). In the Malaysian context, huge investments amount of money has also been invested have been made by various agencies including private organisations to organise programmes that are designed to enhance graduates’ employability, mainly through various types of graduate employability programmes (EPs). The objective of this paper is to discuss the various conceptualisations of graduate employablity in Malaysia, as well as nd the issues of employability of among Malaysian graduates. Given that employers are one of main among the stakeholders of higher education process, this paper reports research which have been conducted thus far to investigate employer their perspectives on what they see to be the salient characteristics of employability. The paper also highlights the drivers and outcomes of change in the 21st Century workplace as expected by employers. At the same time, tThe paper discusses policies and the wayinitiatives of the Government of Malaysia related to Malaysia Responds towards the changing needs for workplace skills and competencies., as well as the challenges faced by Malaysia in developing competent graduate workforce.